Comparative study on performance characteristics of PM and reluctance machines equipped with overlapping, semi‐overlapping, and non‐overlapping windings - Gundogdu, Tayfun; Komurgoz, Guven (Institution of Engineering and Technology (IET), 2020)
In this study, the compatibleness/effectiveness of the proposed novel semi‐overlapping winding (NSW) topology has been investigated by implementing into different synchronous machine technologies, namely interior permanent‐magnet machine, synchronous reluctance machine (SynRM), permanent‐magnet assisted SynRM, and double‐salient reluctance machine. All considered machines have also been designed with different winding topologies; i.e. integer‐slot distributed winding, fractional‐slot concentrated winding (FSCW) in order to reveal the merits/demerits of the proposed NSWs. A comprehensive electromagnetic performance comparison has been presented. It has been validated that the proposed winding topology promises significant advantages; such as improved efficiency with substantially reduced total axial length, low eddy permanent magnet (PM) loss and low risk of irreversible magnet demagnetisation over conventional winding topologies. It has also been revealed that the implementation of proposed NSWs into the reluctance machines results with higher torque and power output than that of FSCWs.